Modelo de Anderson com repulsão coulombiana nos níveis que se acoplam com o ponto quântico - Hostalácio, Alexandre Vilefort (2019)
In this work, a study of the Anderson model is done for the case of a quantum dot between two electron gases, single-electron transistor (SET), where a Coulombian repulsion term was added at the orbitals that are directly coupled to the quantum dot. The resulting model was treated by the Numerical Renormalization Group technique. The thermodynamic properties of the quantum dot were studied and a preliminary study of the conductance in the linear response regime as a function of the temperature was done. The change in the model Hamiltonian made it necessary to compute manually the initial matrices entering the Numerical Renormalization Group program. In general, the two conduction bands, corresponding to the electric contacts, can be manipulated so that one of them ends decoupled from the quantum dot. With the new term added, this decoupling is impossible, being necessary to reformulate how the conductance is computed. The contribution of the quantum dot to some thermodynamic properties was calculated and studied, with emphasis on the behavior of the Kondo temperature. For the study of the conductance, it was proposed a calculation method that proved very expensive computationally, preventing us to generate data for the case of coupled bands during the time of the Master of Science. However, an analysis of the addition of the Coulombian repulsion in the case of uncoupled bands was done.